Knowledge for a Common World? On the Place of Feminist Epistemology in Philosophy of Education - Claudia Schumann (Education Sciences, 2016)
The paper discusses the place of feminist epistemology in philosophy of education. Against frequently raised criticisms, the paper argues that the issues raised by feminist standpoint theory lead neither to a reduction of questions of knowledge to questions of power or politics nor to the endorsement of relativism. Within the on-going discussion in feminist epistemology, we can find lines of argument which provide the grounds for a far more radical critique of the traditional, narrow notion of objectivity, revealing it as inherently flawed and inconsistent and allowing for the defense of a re-worked, broader, more accurate understanding of objectivity. This is also in the interest of developing a strong basis for a feminist critique of problematically biased and repressive epistemological practices which can further be extended to shed light on the way in which knowledge has become distorted through the repression of other non-dominant epistemic standpoints. Thus, requiring a thorough re-thinking of our conceptions of objectivity and rationality, feminist epistemologies need to be carefully considered in order to improve our understanding of what knowledge for a common world implies in the pluralistic and diverse societies of post-traditional modernity in the 21st century.